Hate thy neighbor : move-in violence and the persistence of racial segregation in American housing - Bell, Jeannine, 1969- (New York : New York University Press, 2016)
This title enhances our understanding of how prevalent segregation and hate-crime remain, and offers insightful analysis of a complex mix of remedies that can work to address this difficult problem.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 1, 2016).
Keywords: Discrimination in housing -- United States; Minorities -- Housing -- United States; Racism -- United States; Society; United States of America, USA; Ethnic minorities & multicultural studies; Human rights & civil liberties